Real-time ultrasound to predict beef carcass retail products of buffaloes - Jorge, A. M. [UNESP]; Andrighetto, C. [UNESP]; Francisco, C. L. [UNESP]; Pinheiro, R. S.B. [UNESP]; Tavares, S. A. [UNESP]; Santos Silva, T. L. [UNESP]; Andrade, C. R.M. [UNESP]; Surge, C. A. [UNESP]; Puoli Filho, J. N.P. [UNESP] (My University, 2010)
Twenty eight Mediterranean buffaloes bulls were scanned with real-time ultrasound (RTU), slaughtered, and fabricated into retail cuts to determine the potential for ultrasound measures to predict carcass retail yield. RTU measures of backfat thickness (FT), ribeye area (REA) and rump fat thickness were recorded three to five days prior to slaughter. Carcass measurements were taken, and one side of each carcass was fabricated into retail cuts. Stepwise regression analysis was used to compare possible models for prediction of either kilograms or percent retail product from carcass measurements and ultrasound measures. Results indicate that possible prediction models for % or kilograms of retail products using RTU measures were similar in their predictive power and accuracy when compared to models derived from carcass measurements. Both FT and REA were over-predicted when measured ultrasonically compared to measurements taken on the carcass in the cooler. Ultrasound measurements of REA and FT had positive correlations with carcass measures of the same traits (r=.96 for REA and r=.99 for FT). Standard errors of prediction currently are being used as the standard to certify ultrasound technicians for accuracy. Regression equations using live weight, REA and FT between 12th and 13th ribs and also over the biceps femoris muscle by ultrasound explained 95% of the variation in the hot carcass weight when measure immediately before slaughter.
Keywords: Backfat thickness; Cutability; Ribeye area; Rump fat